Optical coherence tomography angiography metrics predict normal tension glaucoma progression. Issue 7 (8th March 2022) - Wang, Yu Meng; Shen, Ruyue; Lin, Timothy P.H.; Chan, Poemen P.; Wong, Mandy O.M.; Chan, Noel C.Y.; Tang, Fangyao; Lam, Alexander K.N.; Leung, Dexter Y.L.; Tham, Clement C.Y.; Cheung, Carol Y.
ABSTRACT: Purpose: To prospectively determine the relationship between optical coherence tomography angiography (OCTA) metrics and visual field (VF) progression in eyes with normal tension glaucoma (NTG). Methods: Prospective, cohort study conducted from January 2017 to October 2021. OCTA metrics at the peripapillary region (circumpapillary vessel density (cpVD), vessel diameter index (VDI) and fractal dimension (FD) in the radial superficial capillary network), and the macular region (macular vessel density, foveal avascular zone (FAZ) area, FAZ circularity and macular FD in superficial capillary plexus (SCP) and deep capillary plexus (DCP)), were investigated and measured by a customized MATLAB program. VF was evaluated semiannually using standard automated perimetry. Cox proportional hazards model was used to evaluate the relationship of OCTA metrics at baseline to the risk of NTG progression over time. Results: The cohort included 164 NTG patients (270 eyes), which were followed up for at least 2 years. Over a mean follow‐up period of 48.58 ± 7.98 months, 42 of the 270 NTG eyes (15.56%) developed VF deterioration. Among OCTA metrics at peripapillary region, lower superotemporal cpVD (HR per SD decrease, 1.401; 95% CI, 1.017–1.929) was associated with VF deterioration after adjusting for reported risk factors at baseline. Conclusions: Lower superotemporal cpVD at peripapillary region measured from OCTA improves the prediction of VF deterioration in NTG. These findings provided further evidence to support the prognostic role of OCTA in the risk assessment of NTG progression.